CIRCLE OF COMMUNICATION FOR THE AL-QU 'RAN ABILITY TO MEMORIZE OF STUDENTS AT THE ISLAMIC CENTER FOUNDATION - Hendra Syahputra; Mailin Mailin; Wasis Wiseso Pamungkas; Dwi Rizki Nurkusuma (Universitas Dharmawangsa, 2022)
Reading the Al qur 'an is one way to acquire glory and primacy on the side of god because the Al qur 'an gives a clue in human life. This research aims to find out if the communication of the circle influences the success of reading the Al qur 'an student. Later, research subjects for graduate student Aliyah Tahfizul of the islamic center islamic center was chosen as the research subject and interviewed by fifty (50) people. This type of research was codified by data collection techniques using the document angket method and the likert scale, that is, the